The value of postoperative HLA-DR expression and high mobility group box 1 level in predictive diagnosis of sepsis in percutaneous nephrolithotomy surgery - Hai Feng Hou; Ying Liu; Xiaoyang Zhang; Zhenhua Han; Tianming Chen (Renal Failure, 2022)
Objective To analyze the value of postoperative human leukocyte antigen-DR (HLA-DR) expression and high mobility group box 1 (HMGB1) level in predictive diagnosis of postoperative sepsis for patients with percutaneous nephrolithotomy (PCNL) surgery.Methods The present prospective observational study included 387 patients with renal calculus who received PCNL surgery from January 2017 to October 2020 in our hospital. After exclusion criteria, 33 patients with sepsis and 78 patients with no sepsis remained. All patients received PCNL surgery. Sepsis definition is according to the third international consensus definitions for sepsis and septic shock (Sepsis-3). The data of the HMGB1, c-reactive protein (CRP), interleukin-6 (IL-6), procalcitonin (PCT) and HLA-DR expression were collected within admission and 24 h and 72 h after surgery. Postoperative HMGB1 levels and HLA-DR expression at 24 h and 72 h were respectively compared between the two groups using t test. ROC cure was used to analyze the value of postoperative HLA-DR expression and HMGB1 level in predictive diagnosis of sepsis.Results The positive rate of urine culture and the time of hospitalization time in patients with sepsis were significantly higher than those in patients with no sepsis. Sepsis group had higher levels of HMGB1 at post-24 h ((93.07 ± 11.37) ng/mL vs (75.41 ± 4.85) ng/mL), p < 0.05) and 72 h ((96.58 ± 12.12) ng/mL vs (81.16 ± 8.86) ng/mL), p < 0.05) than nosepsis group. Meanwhile, sepsis group had lower expression of HLA-DR at post-24 h ((50.01 ± 7.42) % vs (69.32 ± 10.58) %), p < 0.05) and 72 h ((54.85 ± 9.45) % vs (69.98 ± 11.00) %), p < 0.05) than non-sepsis group. ROC analysis showed that the HLA-DR expression at postoperative 24 h had highest predictive value in the diagnosis of sepsis, the AUC of HLA-DR was 0.934, cutoff value 56.19%, with sensitivity 89.7%, specificity 81.8%.Conclusion Postoperative HLA-DR and HMGB1 can both be used as a predictive diagnosis of sepsis for patients with renal calculus received PCNL surgery. HighlightsSepsis group had higher levels of high mobility group box 1 at post-24 h and 72 h than nosepsis group.Sepsis group had lower expression of HLA-DR at post-24 h and 72 h than nosepsis group.Postoperative HLA-DR and HMGB1 can both be used as a predictive diagnosis of sepsis for patients with renal calculus received PCNL surgery.